Reflexiones al margen de las tensiones entre los diálogos subjetivos, la aceptación pragmática y los discursos del derecho - Pattaro Amaral, Fernanda (Corporación Universitaria Americana, 2022)
The purpose of this book is to incite a series of reflections on the subjective tensions and discourses of Law in a postmodern society where the act of existing advocates a liquidity between pragmatism supported by the values of consumption as an existential fetish that imprisons existence itself, and anyone who is outside this chain of consumption loses the very character of humanity - legitimized through the logic of consumption. In this moment of narcissism the subject is created - trapped in his own image constructed in front of others with the need to be appreciated and the object of consumption-fetish of his equals. Whoever cannot consume, whoever is outside the chain of consumption loses his status of "citizen"... citizenship contemplates those who are immersed in the game of consumption. This "fetish of capital" (Bautista, 2017) that produces an idolatry towards utopian values and sacrifices social coexistence itself in the name of an economic model, does not admit any other form of development and propitiates moral discourses where those who are absent from the policies of these discourses are marginalized. Is Law as a regulatory discipline - in Foucauldian terms - a participant in this fetishist logic, once this discipline regulates (Foucault, 2012) social relations?